Preschool Children’s Behavioral and Emotional Problems using Pediatric Symptom Checklist (PSC 17) during Distance Learning - Fachmi, Teguh; Dalis Ravida Kustiwa; N. Umi Hani (Jurnal Pendidikan Anak Usia Dini Undiksha, 2022)
Distance learning for early childhood education level causes various issues, one of the issues is behavioural and emotional problems. This problem has become a notion that is nearly never researched. The aim of this research is to analyses children’s behavioural and emotional problems by using Paediatric Symptom Checklist-17 (PSC 17) questionnaire for young children. This research is quantitative research by using questionnaire for collecting data. The questionnaire of PSC 17 also uses to screen Kindergarten school children at risk of behavioural and emotional as early detection to develop strategies to meet their mental health needs. The PSC will be completed by the parents of 71 Kindergarten school children. The PSC also will be spread to the targeted participant by public health care staff. A follow-up interview has conducted with the children with symptoms. A multidisciplinary team formed to analyse the case at hand. The result revealed that 7 from 71 preschool children are positively suspected behavioural, emotional and psychosocial disorder consist of 3 males and the rest 4 are females. Further finding known from interviewed parent of preschool children who suspect behavioural, emotional, and psychosocial disorder revealed that lack of time for parents to accompany distance learning is the main cause. Accompanying children during distance learning is compulsory as an effort to reduce behavioural, emotional, and psychosocial disorder.